2012
DOI: 10.1095/biolreprod.112.099309
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Label-Retaining Perivascular Cells in a Mouse Model of Endometrial Decidualization, Breakdown, and Repair1

Abstract: The human endometrium is incredibly dynamic, undergoing monthly cycles of growth and regression during a woman's reproductive life. Endometrial repair at the cessation of menstruation is critical for reestablishment of a functional endometrium receptive for embryo implantation; however, little is understood about the mechanisms behind this rapid and highly efficient process. This study utilized a functional mouse model of endometrial breakdown and repair to assess changes in endometrial vasculature that accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 27 publications
4
38
0
Order By: Relevance
“…A functional response of endometrial epithelial LRCs upon endometrial repair was also observed in an induced decidualization, breakdown, and repair mouse model [25,26]. Nonetheless, the role of endometrial LRCs in the remodeling processes during pregnancy and postpartum remains largely unknown.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…A functional response of endometrial epithelial LRCs upon endometrial repair was also observed in an induced decidualization, breakdown, and repair mouse model [25,26]. Nonetheless, the role of endometrial LRCs in the remodeling processes during pregnancy and postpartum remains largely unknown.…”
Section: Introductionmentioning
confidence: 95%
“…In an artificial mouse endometrial repair model, LRSC near vasculatures proliferate upon tissue breakdown [25]. On the other hand, LRCs enriched at the distal oviduct and the endocervical transition zone did not respond to endometrial regeneration events [37].…”
Section: Lrsc In the Gestational And Postpartum Endometriummentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, label-retaining techniques have been used to identify slow-cycling, quiescent epithelial, and stromal cells in the female reproductive tract as potential stem cells [26,27,46]. Pericytes in both murine [47] and human [48] endometrium are proposed as a source of mesenchymal stem/ progenitor cells. Several of the aforementioned studies indicate the likelihood that stem/progenitor cells exist at the stromal-myometrial border.…”
Section: Figmentioning
confidence: 99%
“…The LRCs were located in the uterine stroma, and 0.32% of them expressed the stem cell marker c-KIT, while 0.19% of them expressed the pluripotency marker POU5F1 (OCT-4) [35]. Other studies investigated the LRCs in the context of their proliferation potential under the influence of estrogen and their contribution to endometrial decidualization, breakdown, and repair [37,38]. The quiescent nature of LRCs and their proliferation potential identified them as potential stem/progenitor cells in the endometrium.…”
Section: Stem Cells In Endometriummentioning
confidence: 99%